Fundamentals of Digital Logic with Verilog Design - Brown Stephen D (McGraw-Hill, 2003)
Fundamentals of Digital Logic with Verilog Design is intended for an introductory course in digital logic design, which is a basic course in most Electrical and Computer Engineering programs. The authors provide a desirable balance between classical and modern design approaches. Basic concepts are introduced using simple logic circuits, which are designed by using both manual techniques and modern CAD-tool-based methods. Having established the fundamental concepts, more complex, realistic circuits are then designed with the CAD tools. The Verilog language is an integral part of design techniques used throughout the book. Altera's advanced Max plus II CAD systmem (on CD-ROM) and a series of step-by-step tutorials are included